Promover la lectura de obras teatrales a través del blog docente Teatro en red - Blanco Martínez, Alfredo (ISL (Investigaciones sobre lectura, 2016)
Nowadays, schools have a project for young people to acquire a taste and a habit of reading. However, it is also necessary that the educational community is configured as an important piece of the network of reading. For this reason, it is essential to show young people a variety of literature texts to learn and appreciate all literary genres. Probably, the play is the least consumed by teenagers, because they associate that kind of text to the theatrical production, and also, they omit the pleasure of reading it. In this sense, it is important that teachers, professionals and families promote reading plays. In this paper, we examine and describe the project Teatro en red from the perspective of its founders. The teacher blog has the aim to disseminate contemporary theatre and, at the same time, it expects to bring young people to the dramatic world from different perspectives. Specifically, we will focus on promoting reading and we will make a special emphasis on educational and cultural strategies pursued by the blog. In this case, we have used a qualitative methodology to make, on the one hand, a holistic understanding of the subject matter and, secondly, to respond to objectives of the study. With respect to the techniques of data collection, we have used the interview to reveal the voices of two teachers and, also, we have utilised the document analysis to know in depth the blog. For analysis of the data collected, we have started a systematic approach and, also, we have used a process of encoding to set the dimensions and categories that illustrate the work of teachers. In conclusion, we will discover that the blog is a social tool accessible to tell stories and, also, to form a reader taste in theatre between young people.
Keywords: Animación a la lectura; Teatro - Blogs; Theatre; Blog; ICT; Qualitative research